2017
DOI: 10.1590/2317-6369000125515
|View full text |Cite
|
Sign up to set email alerts
|

Distúrbios musculoesqueléticos em extremidades superiores distais entre homens e mulheres: resultados de estudo na indústria

Abstract: Objective: to study the association between musculoskeletal disorders in distal upper extremities (MSDUE) and the variable sex in the plastic industry. Method: cross-sectional study with 577 workers. The MSDUE was defined by the presence of pain in the previous twelve months, lasting for more than one week or having a monthly frequency, causing work restrictions or search for medical care, or severity ≥ 3 (from 0 to 5), in at least one of these regions: fingers, wrists, hands, forearms or elbows. Covariates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 49 publications
1
3
0
11
Order By: Relevance
“…The prevalence of work-related musculoskeletal pain found in the present study was similar to the one reported in previous research with the same category of workers (meatpacking industry employees) 18 . However, the rates found for other categories of workers, such as nursing professionals and plastics industry employees, were different 14,19 . This difference might be mainly attributed to the type and specificity of the respective job activities 20 , including, e.g., ergonomic characteristics, body position, movements performed and taking rest breaks or not.…”
Section: Discussionmentioning
confidence: 88%
“…The prevalence of work-related musculoskeletal pain found in the present study was similar to the one reported in previous research with the same category of workers (meatpacking industry employees) 18 . However, the rates found for other categories of workers, such as nursing professionals and plastics industry employees, were different 14,19 . This difference might be mainly attributed to the type and specificity of the respective job activities 20 , including, e.g., ergonomic characteristics, body position, movements performed and taking rest breaks or not.…”
Section: Discussionmentioning
confidence: 88%
“…Para minimizar impactos à saúde decorrentes da atividade laboral e assim o aparecimento de doenças ocupacionais prejudiciais do bem-estar dos trabalhadores e capazes de afetar o engajamento no trabalho, são necessárias medidas de promoção á saúde dos trabalhadores (7). .…”
Section: Referencial Teóricounclassified
“…Reconhece-se com Sandberg (2) Walton (2) . Ferreira (7) e Limongi-França (5) . E, para identificar as reações e comportamentos sobre QVT frente à mudança organizacional, usou-se a abordagem de Sandberg (2) , Hernandez e Caldas (14) e Silva e Vergara (15) Procedimentos para coleta de dados e cuidados éticos (3-5-6-8) .…”
Section: Referencial Teóricounclassified
“…Em relação aos sujeitos da amostra, verificou-se que os indivíduos apresentaram média de idade de 45,27 anos, sendo a maioria mulheres. Nesse contexto, há estudos mostrando que as queixas tendem a aumentar com a idade 23 e as mulheres são mais propensas a apresentarem distúrbios musculoesqueléticos 24 , bem como tendem a apresentar limiar doloroso menor que dos homens 25 .…”
Section: Introductionunclassified